Cuba y Cataluna : encuentro de pueblos y culturas - Laffita, Bárbara B.; García, Carlos A.; Sánchez, Alejandro (La Habana, Cuba : Editorial UH, 2013)
Meet Rose Devonic, a wily, ferociously determined twenty-nine-year-old woman. In the tiny mountain town of Queduro, New Mexico, she makes her living selling traditional embroidery. But Rose has no home or family. In winter she sleeps in a mostly abandoned motel, and in summer she lives out of her car. A tragedy in her past, which is a constant reminder to her neighbors of their complicity, has made her an outcast who trusts nothing except her own ability to survive. One frozen afternoon in October, Rose hitches a ride over the already snow-covered mountain pass and walks the last four miles of the road to her hometown of Queduro. Her monthlong fling with Harmon Waters - yet another disappointment - is over, and once again she must pick up the pieces of her life. But when she arrives at the Ten Tribes Motel, even Birdie, her elderly landlord and best friend, seems dismayed to see her.
Notas antes del encuentro / Bárbara B. Laffita / Carlos A. García / Alejandro Sánchez EL ENCUENTRO DE DOS CULTURAS. Una introducción necesaria para el estudio de la inmigración de españoles a Cuba y sus asociaciones / María del Carmen Barcia Zequeira / Alejandro García Álvarez Encuentro histórico de Cuba y Cataluña / Joan M. Ferrán Oliva CATALUÑA EN CUBA. Los catalanes de la Habana / Ernesto Chávez La influencia catalana en Guantánamo desde el siglo XIX hasta 1940 / Irina Fontanet Gil El comercio catalán en la ciudad de Santiago de Cuba en el periodo de 1860 a 1894 / Yuliet Góngora Blanco Cataluña en Matanzas. Los exvotos de Monserrate / Clara Emma Chávez Álvarez CUBA EN CATALUÑA: LOS INDIANOS Cuba en Badalona / Jaume Aymar I Ragolta Contribución al estudio de los <<indianos>> del Baix Empordá: los Pallimonjo de Calonge / Ernesto Álvarez Blanco El legado cubano en Cataluña y la nueva aristocracia creada a partir de la llegada de capital desde Cuba (SS. XVIII-XX) / Tate Cabré Massot LA IDEOLOGIA CATALANA EN CUBA. Prensa y nacionalismo catalán en la Cuba del Siglo XIX / Lluís Costa I Fernández Desde Cuba: Conangla i Fontanilles y Pi i Margall / Xavier Ferré I Trill Repercusión de los exiliados republicanos en la comunidad catalana de Cuba / Jorge Domingo Cuadriello CATALUÑA EN LA PALABRA DEL CUBANO. La presencia lingüística de Cataluña en Cuba / Sergio Valdés Bernal Catalanes en la odonimia habanera / Adianys Collazo Allen EL ENCUENTRO EN LA ARTES. Valencia y la Habana. Apuntes sobre un diálogo / Anelys Álvarez Muñoz El coleccionismo privado de pintura moderna catalana y valenciana en la Habana / Bárbara B. Laffita El Eixample de Barcelona y El Vedado, momentos del urbanismo en el Siglo XIX. Vigencia actual / Meilyn Yanes Vega / Ariel Díaz Piedras
Keywords: CUBANOS -- ESPAÑA -- CATALUÑA; CATALANES -- CUBA; ENSAYOS CUBANOS; ENSAYOS ESPAÑOLES; CUBA -- RELACIONES -- ESPAÑA -- CATALUÑA; CATALUÑA (ESPAÑA) -- RELACIONES -- CUBA